Sb-doped titanium oxide: a rationale for its photocatalytic activity for environmental remediation - Zimbone, M; Cacciato, G; Spitaleri, L; Egdell, RG; Grimaldi, MG; Gulino, A (American Chemical Society, 2018)
The problem of water purification is one of the most urgent issues in developing countries, where large infrastructures and energy resources are limited. Among the possibilities for a cheap route to clean water, photocatalytic materials in the form of coatings or nanostructures are among the most promising. The most widely studied photocatalytic material is titanium dioxide (TiO2). Here, we investigate the photocatalytic properties of 1.5% Sb-doped TiO2 and laser-irradiated Sb-doped TiOx. Calcined Sb-doped TiO2 was found to adopt the rutile structure, but it turned amorphous after laser irradiation. Photocatalytic tests for Sb-doped TiO2 showed an activity 1 order of magnitude higher than that of an undoped TiO2 control sample under both ultraviolet and visible irradiation. A further sizeable enhancement resulted from laser irradiation. The increased photocatalytic activity is ascribed to both enhanced visible region absorption associated with Sb-induced lone pair surface electronic states and trapping of the holes at the lone pair surface sites, thus inhibiting the recombination of the electrons and holes generated in the initial photoexcitation step. This study shows the first rationalization of the photocatalytic properties of Sb-TiO2 in terms of its electronic structure.